The verb as a bearer of emotional education in lecture halls (Cahiers Africains de rhétorique, 2025)
: Speaking of the verb in the academic field seems obvious where teachers build generations of individuals capable of transforming the world. Such an undertaking cannot be achieved without this essential tool: language, which resonates through speech. Considering the complexity of human beings, it goes without saying that speech can take different forms and serve different purposes. Here, we propose to explore a beneficial use of it to support the psychological dimension of learners in the higher education system of Côte d'Ivoire. Indeed, it is a concrete matter of emphasizing the role of speech in the emotional education of our learners. Also, our article will lead us to answer the following questions: Does speech play a role in the implementation of emotional education? If so, what are its applications and manifestations? Furthermore, could it allow learners to develop resilience to the difficulties they face? In response to these questions, we hypothesize that speech plays an important role in this area, that it can alleviate learners' pain and that it can help develop resilience in learners. The objectives of this study are therefore to reveal the role of this faculty, its applications and manifestations, as well as to demonstrate the resilience it can bring to students.